DEFINISI SENI ACHDIAT K. MIHARDJA DAN APLIKASINYA PADA SENI KRIYA - Sumadi Sumadi (Ornamen, 2005)
Karta Mihardja makes an art definition caused by his worry, at that time the cultural art condition and the personality of Indonesian nation in a state of labile. His aim is to form the image of virtuous Indonesian nation the theme â€œartistic definition of Karta Mihardja and his application at fine artâ€ instructed as creation base form fine art (contemporary art), as distinguishment with the tradition of art product in global era.Keyword:artistic, contemporary, tradition